PERAN KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN MOTIVASI KERJA GURU (STUDI KASUS SEKOLAH DASAR NEGERI 2 BLIMBING KECAMATAN BOJA) - Rudy Widyanarko; Noor Miyono (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The purpose of writing this article is to find out whether the problem of school principal leadership in increasing teacher work motivation in order to advance the quality of education is a problem that must be overcome. Work motivation at SDN 2 Blimbing, Boja District is still not good because it can be seen from the teacher's lack of enthusiasm for work as evidenced by the fact that several teachers are still not properly responsible in carrying out their duties. Teachers rarely make RPPs, because teachers only make RPPs when there will be supervision, this is because there are a lot of assignments and teachers go home until the afternoon. Not only that, the next problem is that there are still some teachers who lack preparation in teaching, such as: teachers do not prepare materials or materials a week in advance but the lesson materials, methods and learning models are determined a few minutes before entering class. Therefore, the problem of teacher work motivation needs to be considered and supervised by the principal, where the principal must be able to apply leadership in increasing teacher work motivation in accordance with the conditions in the environment. Solving this problem will be followed by a positive impact on teachers, the surrounding community, including the Kaligading 1 State Elementary School, Boja District, The implication of this research is that the school principal's democratic leadership in increasing teacher work motivation needs to be improved to improve the quality of student education in the Blimbing 2 State Elementary School (SD) environment. If the democratic leadership used by the school principal increases then it can be ensured that teacher work motivation will also increase, thereby having an impact. the quality of education produced will be better.